Analisis Aksi Spiritual Tanggap Covid-19 Selama PPKM di Pondok Pesantren Al-Jihad Surabaya - Muhammad Ghufron; Ahmad Rizkiansah Rahman; Mochammad Asep Robbi Achmat; Novita Mulya Sari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
Since the Covid-19 pandemic at the end of 2019 in China, the entire life order of the world's people has changed drastically. Along with the increasing number of patients exposed to Covid-19 and the number of patients who died and the enactment of the Policy for the Enforcement of Community Activity Restrictions on the island of Java-Bali in accordance with the Instruction of the Minister of Home Affairs Number 01-04 of 2021, it turned out to be increasing anxiety and health problems. mentality for society. Based on these conditions, it is very necessary to have various aspects of treatment ranging from prevention, recovery, and also overcoming the emergence of anxiety disorders. The importance of Islamic boarding schools as Islamic educational institutions in these conditions will be a fortress of faith and immunity in the face of Covid-19. The spiritual action analyzed was the practice of remembrance of the Covid-19 rejection certificate from KH. The practice of this remembrance indirectly has a considerable influence on the physical condition of the congregation who follows the practice of remembrance. The panic experienced by the public regarding the increasing mortality rate during the PPKM period can be quelled by the peace of mind that results from the practice of this remembrance. Therefore, the mental and physical health of the community will be maintained without ignoring the health protocols determined by the government.Keywords: Spiritual action; PPKM; Physical and Mental Health. AbstrakSejak pandemi Covid-19 muncul pada akhir tahun 2019 di China, seluruh tatanan kehidupan masyarakat dunia berubah drastis. Seiring dengan meningkatnya jumlah pasien terpapar Covid-19 dan jumlah pasien yang meninggal serta diberlakukannya Kebijakan Pemberlakuan Pembatasan Aktivitas Masyarakat di Pulau Jawa-Bali sesuai Instruksi Menteri Dalam Negeri. Nomor 01-04 Tahun 2021 ternyata meningkatkan kecemasan dan masalah kesehatan serta mental bagi masyarakat. Berdasarkan kondisi tersebut maka sangat diperlukan berbagai aspek penanganan mulai dari pencegahan, penyembuhan, pemulihan, dan juga mengatasi munculnya gangguan kecemasan. Pentingnya Pondok Pesantren sebagai lembaga pendidikan Islam dalam kondisi seperti ini akan menjadi benteng iman dan imun dalam menghadapi Covid-19. Tindakan spiritual yang dianalisis adalah amalan zikir surat keterangan penolakan Covid-19 dari KH. Amalan zikir ini secara tidak langsung memiliki pengaruh yang cukup besar terhadap kondisi fisik jemaah yang mengikuti amalan zikir. Kepanikan yang dialami masyarakat terkait meningkatnya angka kematian selama periode PPKM dapat diredam dengan ketenangan jiwa yang dihasilkan dari pengamalan zikir ini. Dengan demikian, kesehatan mental dan fisik santri maupun masyarakat akan tetap terjaga tanpa mengabaikan protokol kesehatan yang telah ditetapkan pemerintah.Kata Kunci: Aksi Spiritual; PPKM; Kesehatan Fisik dan Mental.